Effects of Ionic Liquid and Biomass Concentration to Partial Vapour Pressure Change in Hydrothermal Carbonization - Nongnoot Srilek (2020)
© Published under licence by IOP Publishing Ltd. This study aims to investigate the effects of ionic salt liquid and biomass concentration to partial vapour pressure change in hydrothermal carbonization system. The durability of reactor and safety aspect are crucial point for constant volume system which pressure is independence and important in scaling up hydrothermal process. The ionic salt including calcium propionate with the molality of 0.33, 0.43 and 0.65 and sodium chloride with the molality of 0.86, 1.14 and 1.71 were used. The suspension of corncob biomass and deionized water with the ratio 1:20 and 1:10 also were evaluated. The partial vapour pressure of the solution of sodium chloride with the molality of 1.71 decrease for 12.5 %. The partial vapour pressure of corncob biomass concentration with 1:20 decrease for 2.8%. The hydrochar produced from the 240 °C of reaction temperature and 100 minutes reaction time demonstrated the gradually decrease of hemicellulose constituent corresponding with higher biomass concentration.